2017
DOI: 10.1371/journal.pone.0184573
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to mosquito host sex and parasite dosage suggest mixed dispersal strategies in the parasite Ascogregarina taiwanensis

Abstract: Mixed dispersal strategies are a form of bet hedging in which a species or population utilizes different dispersal strategies dependent upon biotic or abiotic conditions. Here we provide an example of a mixed dispersal strategy in the Aedes albopictus / Ascogregarina taiwanensis host/parasite system, wherein upon host emergence, the gregarine parasite is either carried with an adult mosquito leaving the larval habitat, or released back into the larval habitat. We show that the parasite invests a larger proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…used by A. taiwanensis based on host sex and environmental cues [27]. While Ascogregarine parasites in mosquitoes have served as a model system to investigate the evolutionary biology and physiological impacts of parasitism, their association with the composition of the mosquito microbiome and potential use as a biocontrol [22] remains poorly resolved.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…used by A. taiwanensis based on host sex and environmental cues [27]. While Ascogregarine parasites in mosquitoes have served as a model system to investigate the evolutionary biology and physiological impacts of parasitism, their association with the composition of the mosquito microbiome and potential use as a biocontrol [22] remains poorly resolved.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…triseriatus was found in one study to have as high as 2.8 to 3.5 greater death rates when infected [25]. In a relatively recent study by Soghigian and Livdahl [51], they show that in the absence of parasite infection, survival of Ae. albopictus is about 98%, but with the greatest amount of infection observed, the survival decreases to approximately 71%.…”
Section: Albopictusmentioning
confidence: 90%
“…The effects of parasitism for Ae. albopictus on female fecundity (Îł ba ), larval development rate (Îł da ), and larval mortality (Îł ma ) were shown to vary with resource availability and environmental context [23,7,25,51]. In Comiskey et al [23], they found that in low resources the mortality of infected Ae.…”
Section: Albopictusmentioning
confidence: 98%
See 1 more Smart Citation
“…triseriatus , infection can alter larval behaviour (Soghigian, Valsdottir, & Livdahl, ), prolong female development time (Walker, Poirier, & Veldman, ) and decrease adult size (Siegel, Novak, & Maddox, ; Walker et al, ). These indirect effect can potentially reduce mosquito fecundity and population growth (Soghigian & Livdahl, ). Field and laboratory surveys indicate few As .…”
Section: Methodsmentioning
confidence: 99%